2020
DOI: 10.1111/jph.12934
|View full text |Cite
|
Sign up to set email alerts
|

Development of SSR markers from transcriptome data for the pear rust pathogenGymnosporangium asiaticum

Abstract: The pear‐cypress rust Gymnosporangium asiaticum is one of the most significant causal agents of pear rust in Asian pear, severely affecting the pear industry. Research on the genetic diversity of this widespread pathogen has been hampered due to the absence of molecular markers. In the current study, we developed 16 novel microsatellite markers for G. asiaticum from transcriptome data by combining next‐generation sequencing and PCR screening. These polymorphic markers were tested on 96 individuals from nine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Currently, RNA-seq has been used in the SSR development of G. yamadae and G. asiaticum ( Tao et al, 2018 ). EST-SSR can detect numerous alleles, with high repeatability and inter-species transferability due to the presence of microsatellites regions throughout the transcriptome ( Weng et al, 2020 ). In addition, EST-SSR can display the functional information of the sample genome, and the sequences identified in the homologous genes are more conserved, so it has the characteristics of large amount of information, good universality and simple development ( Wu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, RNA-seq has been used in the SSR development of G. yamadae and G. asiaticum ( Tao et al, 2018 ). EST-SSR can detect numerous alleles, with high repeatability and inter-species transferability due to the presence of microsatellites regions throughout the transcriptome ( Weng et al, 2020 ). In addition, EST-SSR can display the functional information of the sample genome, and the sequences identified in the homologous genes are more conserved, so it has the characteristics of large amount of information, good universality and simple development ( Wu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic SSR locus analysis revealed that tri-nucleotide repeats had the highest occurrence frequency, accounting for 52.53% of the repeats, which aligns with the results of previous reports on other fungi ( Qian et al, 2013 ). However, tetra-nucleotide repeats tend to stutter less than tri-nucleotide and di-nucleotide repeats and are markedly more accurate and reliable ( Weng et al, 2020 ). Therefore, one of the principles in selecting EST-SSR primers of S. rolfsii involved the selection of a sequence with a repeat unit of di- to penta-nucleotides to increase diversification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation